Batracobdella leeches, environmental features and Hydromantes salamanders. Issue 1 (April 2018) - Lunghi, Enrico; Ficetola, Gentile Francesco; Mulargia, Manuela; Cogoni, Roberto; Veith, Michael; Corti, Claudia; Manenti, Raoul
Abstract: Leeches can parasitize many vertebrate taxa. In amphibians, leech parasitism often has potential detrimental effects including population decline. Most of studies on the host-parasite interactions involving leeches and amphibians focus on freshwater environments, while they are very scarce for terrestrial amphibians. In this work, we studied the relationship between the leech Batracobdella algira and the European terrestrial salamanders of the genus Hydromantes, identifying environmental features related to the presence of the leeches and their possible effects on the hosts. We performed observation throughout Sardinia (Italy), covering the distribution area of all Hydromantes species endemic to this island. From September 2015 to May 2017, we conducted >150 surveys in 26 underground environments, collecting data on 2629 salamanders and 131 leeches. Water hardness was the only environmental feature correlated with the presence of B. algira, linking this leech to active karstic systems. Leeches were more frequently parasitizing salamanders with large body size. Body Condition Index was not significantly different between parasitized and non-parasitized salamanders. Our study shows the importance of abiotic environmental features for host-parasite interactions, and poses new questions on complex interspecific interactions between this ectoparasite and amphibians. Graphical abstract: Image 1 Highlights: Sardinian Hydromantes salamanders are often parasitized by Batracobdella algira . Underground presence of B. algira is strongly associated to active karstic systems. Leeches often parasitize large-sized salamanders. Parasitism of B. algira does not affect Body Condition Index of salamanders.